The Effect of Search, Solve, Create, And Share (SSCS) Learning Models Assisted Multimedia Interactive to Improve Creative Thinking Ability and Student Learning Outcomes - Maimun Maimun; Bahtiar Bahtiar (Postgraduate, University of Mataram, 2022)
The educational curriculum facilitates students to improve their abilities in dealing with the 4.0 era, where students are asked to get used to solving problems, critically, and creatively. The purpose of this study was to determine the effect of the Search, Solve, Create, and Share (SSCS) Learning Model Assisted by Interactive Multimedia to improve Creative Thinking Ability and Learning Outcomes of MAN 1 Mataram Students. The type of research used is a quasi-experimental (quasi-experimental). Place and Time of Research The research was conducted at MAN 1 Mataram. The study was conducted from 12 February to 17 April 2022. The population in this study were all students of class X MAN 1 Mataram which consisted of 2 classes with a total of 64 people. The steps taken in experimental research are: (1) giving a pretest to both groups; (2) perform the treatment by applying the interactive multimedia assisted SSCS model in the experimental group and the SSCS learning model in the control group; (3) give posttest to both groups. The research design used a nonrandomized control group pretest-posttest design. The analytical technique used is SPSS consisting of Levene univariate homogeneity test, Kolmogorov Smirnov normality test. Furthermore, the analysis of the effect of treatment on each group uses the paired t-test with the condition that the decision is made if the value of Sig <0.05. The last step is to test the difference in the final ability in the two classes using an independent t test with the condition that the decision is made if the value of Sig < 0.05. The results showed that the results of the difference test in the control group and the experimental group showed that there was an effect of using the Search, Solve, Create, and Share (SSCS)Â Model.